Commercial diplomacy, cultural encounter and slave resistance : episodes from three VOC slave trading voyages from the Cape to Madagascar, 1760-1780 - Alexander, Andrew (Department of Historical Studies, 2014)
The intention of this dissertation is to fill a gap in a rich and yet under-represented aspect of Indian Ocean slave history. A number of historians have devoted their attention to the history of slave trading on the island of Madagascar; however, most of these focus on either the 17th or the 19th centuries, leaving the 18th century relatively neglected. In addition, these studies are largely in the form of historical surveys, encompassing a temporal span of many decades. Thus, my purpose has been to adopt a different approach to the study of European-initiated slave trading expeditions to Madagascar to those that have preceded it. I have elected to found this study on a close reading of two journals from slave trading vessels that sought slaves for the Cape in Madagascar in the 1760s and the 1770s. In addition, I have incorporated material from my research on a third vessel that I completed for the purposes of my Honours degree. The first two vessels are De Neptunus , which sailed from 1760-1761, and De Zan, which sailed from 1775-1776. The third vessel is the Meermin, which sailed from 1765-1766. I have undertaken a close reading of the journals maintained by the merchants of De Neptunus and De Zan, so as to write a history sensitive to the daily experiences of the slave traders in Madagascar, as well as to the codes and discourse through which this experience was filtered. Regarding the Meermin, I have not examined its actual voyage to Madagascar as such, but have investigated a slave uprising that occurred on the vessel on its return home in 1766. I have organised this dissertation into three chapters, systematised thematically. The first is concerned with the experience of negotiation and trading as it was recorded by the VOC merchants on the vessels, and is drawn predominantly from the first trading encounter of the crew of De Zan when they arrived in Madagascar in 1775. The second explores the predicaments that the European slave traders encountered on the island, predicaments that arose both from cultural misunderstandings and from personal conflict with the Malagasy. I have drawn on episodes from De Zon and De Neptunus to illustrate this theme. In the third and final chapter, I analyse the phenomenon of slave resistance on board slave ships, using a slave uprising that occurred on De Zan while it was still on the coast of Madagascar, and that of the Meermin when it was approaching Cape Agulhas, as two distinct and yet mutually informative examples of this phenomenon. In contrast to the surveys that comprise the majority of the English-language scholarship on slave trading in Madagascar, this dissertation is founded on a close reading of particular episodes, some relatively peaceful, some fraught with tension, some even violent, all of them revealing. In a sense, it is an attempt at a series of micro-narratives that illustrate and detail the historical experience of VOC-slave trading on the island at a particular juncture and from a variety of perspectives. As such, there is more of a focus on character and incident that there is on the economics and materiality of the trade; and it is in this emphasis that this study seeks to find itself a place in the scholarship on this fascinating and multi-layered cultural encounter.